Law and torture : widening the apertures from the doctrinal to the critical / Ergün Cakal. - Cakal, Ergün (Law in context., 2026)
Legal books on torture have failed to ask fundamental questions as to its practice and research - particularly on the factors informing how torture comes to be defined and how torture victims should appear. This book arms readers with questions in critically exploring these factors.